2015
DOI: 10.1097/md.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Retinopathy of Prematurity in Multiple Gestations

Abstract: To determine the incidence and risk factors of retinopathy of prematurity (ROP) among new-born Chinese infants of multiple gestations.A retrospective review of medical records was performed for all neonates of multiple gestations screened for ROP between January 2007 and December 2012 in 2 neonatal intensive care units in Hong Kong. Screening was offered to very low birth weight (VLBW; ≤1500 g) and/or preterm (gestation ≤32 weeks) neonates using the Royal College of Ophthalmologists ROP guideline and the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 17 publications
1
31
2
2
Order By: Relevance
“…In our study, the incidence of ROP among VLBW infants with GA < 32 weeks was 30.5%, similar to the incidence reported in Saudi Arabia (37.4%) by Binkhathlan et al 13 The incidence of stage ‡3 ROP in our study was 3.2%, significantly higher in infants delivered at <32 weeks or with BW < 1000 g and consistent with the findings of other Chinese studies. 14,15 Moreover, no infant had stage 4 or stage 5 ROP in our study. With the increased awareness of the risk of blindness caused by ROP, the Chinese Ministry of Health guidelines for the prevention and treatment of ROP were published in 2004.…”
Section: Distribution Of Rop In Vlbw Infantsmentioning
confidence: 52%
See 1 more Smart Citation
“…In our study, the incidence of ROP among VLBW infants with GA < 32 weeks was 30.5%, similar to the incidence reported in Saudi Arabia (37.4%) by Binkhathlan et al 13 The incidence of stage ‡3 ROP in our study was 3.2%, significantly higher in infants delivered at <32 weeks or with BW < 1000 g and consistent with the findings of other Chinese studies. 14,15 Moreover, no infant had stage 4 or stage 5 ROP in our study. With the increased awareness of the risk of blindness caused by ROP, the Chinese Ministry of Health guidelines for the prevention and treatment of ROP were published in 2004.…”
Section: Distribution Of Rop In Vlbw Infantsmentioning
confidence: 52%
“…After adjusting for confounding factors, IVF increased the risk of ROP by approximately two times, consistent with some domestic and international studies. 14,18 Watts and Adams 18 showed that assisted conception using IVF rather than gonadotrophin stimulation appears to be the major risk factor for the development of threshold ROP. Yau et al 14 also found that IVF was an independent risk factor for type 1 ROP (OR ¼ 6.17; 95% CI 1.15-45.83).…”
Section: Maternal Obstetric Factors and Ropmentioning
confidence: 99%
“…Los recién nacidos que presentaron retinopatía de la prematuridad fueron 48 (25,26%), siendo la edad gestacional menor de 28 semanas al nacer y el peso menor a 1.000 gramos; antecedentes similares reportados por Port y Yau (18,19) . En el estudio realizado por Fernández R, se reportó 30,8% para los menores de 1.500 gramos al nacer (20) .…”
Section: Discussionunclassified
“…Known risk factors include small gestational age (GA) [4], anemia, blood transfusion, mechanical ventilation [5], hypoxemia [6], perinatal sepsis [7], use of inotropes [8], intra-ventricular hemorrhage (IVH), low birth weight [9], and postnatal exposures [10]. Limited literature is available regarding ROP development among twin pairs [11]. Our study aims to determine profile of asymmetry of ROP among twins the newer post natal risk factors and effects of current treatment responsible for the variability in ROP.…”
Section: Introductionmentioning
confidence: 99%